Effects of dietary nitrate and nitrite on growing-finishing pigs - Sukhonthasarnpa, S.; Parrish, D.B.; Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
The presence of nitrates and nitrites in feed and drinking water of farm animals apparently has caused some serious nutritional problems. This study was to establish more clearly some ways the nitrites interfere with normal processes in the animal body.
Keywords: Swine; Nitrate; Nitrite; Growing-finishing pigs